Someone is pulling the strings: hypersensitive agency detection and belief in conspiracy theories. (2nd January 2016) - Douglas, Karen M.; Sutton, Robbie M.; Callan, Mitchell J.; Dawtry, Rael J.; Harvey, Annelie J.
Abstract: We hypothesised that belief in conspiracy theories would be predicted by the general tendency to attribute agency and intentionality where it is unlikely to exist. We further hypothesised that this tendency would explain the relationship between education level and belief in conspiracy theories, where lower levels of education have been found to be associated with higher conspiracy belief. In Study 1 ( N = 202) participants were more likely to agree with a range of conspiracy theories if they also tended to attribute intentionality and agency to inanimate objects. As predicted, this relationship accounted for the link between education level and belief in conspiracy theories. We replicated this finding in Study 2 ( N = 330), whilst taking into account beliefs in paranormal phenomena. These results suggest that education may undermine the reasoning processes and assumptions that are reflected in conspiracy belief.